If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(w-2)=-7w+36
We move all terms to the left:
4(w-2)-(-7w+36)=0
We multiply parentheses
4w-(-7w+36)-8=0
We get rid of parentheses
4w+7w-36-8=0
We add all the numbers together, and all the variables
11w-44=0
We move all terms containing w to the left, all other terms to the right
11w=44
w=44/11
w=4
| t(5/8)+14=-11 | | 9x-10+x+3=3 | | 2+3x=7x-12 | | 9=x-10+x+3 | | (2)/(3)-x+5x=(1)/(2)+x | | 2x-3x+7=-3-7 | | (2/5)t+21=15 | | 3n+10=14 | | 8x-1=-2x+82 | | 8x-1=-2x-82 | | 6r-2r-15=25 | | 12x+-2=134 | | 12x-2=134 | | 6r-2r-15=40 | | 12(x-3)=-3(x-27) | | 323=89y-78y+3y | | 63=15x+42 | | 6d−211=2d−21/3 | | -6u+4(u-8)=-36 | | 6x+4+3x=4x+19 | | x−.3x=21.70 | | 381057=3E+08x+106026 | | 3(r)=12 | | 5x+6=4x^2 | | 4(y+7)+2y=-14 | | (7x)^(-2/3)=16 | | 1.1x+7-4.1x=10 | | x^=8-5x | | 3b+4=5b–12 | | 24x-16=12x+8 | | 3•x+8=29 | | (x^2-6x)^2-35(x^2-6x)-200=0 |